ANALISIS RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS DENGAN STRUKTUR KEPEMILIKAN SEBAGAI VARIABEL MODERASI - Felicia Komala; Yustina Triyani (Jurnal Akuntansi, 2019)
Financial distress is a steep decrease in the company's financial condition before the company went bankrupt. Financial distress can be analyzed through financial ratios and the ownership structure of the company. This study used logistic regression analysis. The sampling technique is non-probability sampling using a purposive sampling method. The study sample consisted of 70 companies on the Stock Exchange from the 2015-2017 period. Based on regression, Grover, the Springate model showed that the model can predict the value of observation. The results indicate there is sufficient evidence that tends to leverage positively affects both financial distress with Grover and Springate model, a firm's growth tends to negatively affect financial distress with the Springate model, and institutional ownership tends to weaken the influence of leverage to financial distress with Springate model. On the other hand, there is not enough evidence that the firm's growth tends to negatively affect the financial distress with the Grover model. Managerial ownership does not affect moderate leverage and growth of the firm towards better financial distress with the Grover and Springate model. Institutional ownership does not affect moderating leverage of financial distress relationship with the Grover model. Institutional ownership does not affect the firm's growth to moderate the relationship financial distress with Grover or Springate model.Keywords: Financial ratio analysis, Ownership structure, Financial distress